SIMAGRI: An Agro-climate Decision Support Tool - Faniriantsoa, Rija; Grossi, Amanda (2022)
The SIMAGRI training workshop aimed to build the capacities of agricultural/agro-meteorological experts from MoA, EIAR, and EMI (Ethiopian Meteorology Institute) in applying the SIMAGRI tool for agricultural climate risk management and decision support. The specific objectives include 1) participants better understand available seasonal climate forecast information, including how they are generated and their potential/limitations for agricultural decision-making; 2) participants are equipped with background knowledge of the SIMAGRI tool, including the theory and concept of crop modeling and temporal downscaling of tercile probabilistic seasonal climate forecasts; 3) participants can use the SIMAGRI tool expertly and understand how to interpret results of the "what-if" scenario analyses.